Forest products : annual market review 2019 - 2020 - United Nations. Economic Commission for Europe (UNECE); United Nations.; Food and Agriculture Organization of the United Nations (FAO) (Geneva: United Nations, 2020)
b
1. Economic overview and policies -- 2. Wood raw materials -- 3. Sawnwood -- 4. Wood-based panels -- 5. Pulp and paper -- 6. Wood energy -- 7. Value-added wood products -- References -- Annexes.
Keywords: Lumber trade; North America; Europe; Forest products